Data on microstructural and optoelectronic properties of electrodeposited silver mesh transparent conducting electrodes - Seoin Kang; Choong-Heui Chung (Data in Brief, 2023)
Electrodeposited Ag mesh transparent conducting electrodes (TCEs) based on self-cracking templates can achieve high optical transmittances and low sheet resistances by controlling the shape of the self-cracking templates and electrodeposition duration. The surface coverage of the mesh is mainly determined by the surface shape of the self-cracking template. Electrodeposition of Ag can adjust the thickness of the mesh, significantly reducing the sheet resistance while maintaining the high optical transmittance of the TCEs. The TCE electrodeposited for 30 s exhibited an optical transmittance as high as 88.4% and a sheet resistance as low as 2.24 Ω/□. Here we provide the microstructural and optoelectronic performance data of the electrodeposited Ag mesh TCEs.